Evaluasi Keterampilan Kader dalam Pengukuran Antropometri pada Bayi dan Balita - Susanah, Susi; Astutik, Reni Yuli; Suryani, Triska Fajar (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Posyandu (community health post) cadres in villages such as Wanakarta, within the Lolongguba Health Center working area, serve as the frontline in monitoring children’s nutritional status. However, observations indicate that cadres often lack accuracy in using anthropometric tools and do not fully comply with standardized procedures, resulting in measurement errors. Objective: This study aimed to evaluate the skills of Posyandu cadres in conducting anthropometric measurements for infants and toddlers by applying Fishbone and SWOT analyses. Method: The activity was implemented using a Health Education Session Plan (Satuan Acara Penyuluhan, SAP). The topic was “Evaluation of Cadres’ Skills in Conducting Anthropometric Measurements on Infants and Toddlers,” involving all cadres in Wanakarta Village. Lectures and discussions were conducted at the Wanakarta Village Hall from September 22 to October 22, 2025, with the main session held on October 11, 2025. Result: The intervention successfully improved cadres’ competencies in weight, height/length, and mid-upper arm circumference measurements. After educational sessions, mentoring, and practical demonstrations, cadres demonstrated better adherence to standard procedures. SWOT Analysis highlighted opportunities for sustainable skill enhancement through continuous training, improved supervision, and strengthened cross-sectoral collaboration. Conclusion: Structured training and mentoring effectively enhanced anthropometric measurement skills among Posyandu cadres. Improved accuracy in data collection supports better growth monitoring in the Kartu Menuju Sehat (KMS). Ensuring sustainability requires ongoing support, adequate equipment, and motivation for cadres to maintain high-quality Posyandu services and early detection of nutrition problems in the community.